Perancangan Alat Smart Trash Bin untuk Pembakaran Sampah Berbasis SMS Gateway - Sirait, Rummi Santi Rama (KILAT, 2024)
Waste accumulation is one of the problems faced by urban communities, where garbage accumulation can cause environmental pollution and health problems in the community. This research will design a garbage combustion tool that works automatically that can be monitored at the height of the waste and process the burning of the garbage through the SMS Gateway. The working device on the system consists of a power supply, LM35 sensor, AC voltage dimmer, heating element, infrared proximity sensor, SIM900l GSM/GPRS shield, DC-DC converter, ZMPT101B voltage sensor, ACS712 current sensor, and Arduino UNO R3 microcontroller. Results show the performance of the process of burning the waste is carried out with conditions at the level of the height of waste and conditions based on a load of waste. To the height of waste, PWM is set at 150 at a height of 25%, 200 at a height of 50%, and 255 at a height of 75% for different types of waste, namely plastic, combination, styrofoam, and paper. Overall the tool can work for burning garbage with a 500-gram load/process, with an average of 500 watts of power generated and a burning time of 5 minutes.